OPTICAL SPECTROSCOPIC STUDY OF TUHUALITE AND A RE-EXAMINATION OF THE BERYL, CORDIERITE, AND OSUMILITE SPECTRA - Taran M.N.; Rossman G.R. (My University, 2001)
Polarized optical absorption spectra of a rare Fe2+, Fe3+-bearing silicate mineral, tuhualite, (Na,K)2Fe22+Fe23+Si12O30, were measured at room temperature in the range 350–4000 nm (ca. 28500–2500 cm–1). The spectra display a number of strongly pleochroic absorption bands in the visible and NIR range, which are attributed to ferric and ferrous ions distributed over octahedral and tetrahedral sites in the structure. No absorption bands caused by H2O or OH stretching vibrations have been observed in the 3000 to 4000 cm–1 range. A narrow, weak absorption line at ~422 nm (γ ≈ β) is attributed to the 6A1g → 4A1g,4Eg spin-forbidden transition of six-coordinated Fe3+ ions that occupy the octahedral Fe2 position of the tuhualite structure. A broad, intense band at ~573 nm (γ > β >> α) is assigned to a Fe2+/Fe3+ intervalence charge transfer transition (IVCT) between tetrahedral Fe2+ and octahedral Fe3+. Together with the high-energy absorption edge, the band at 573 nm causes the intense violet color and spectacular pleochroism (γ > β >> α) of tuhualite. An intense band at ~1040 nm (γ > β >> α) and a much weaker band ~ 2150 nm (α) are attributed to spin-allowed dd transitions of Fe2+ in the strongly distorted tetrahedral Fe1 sites. On the basis of the data obtained for tuhualite, optical spectra of the structurally related minerals beryl, cordierite, and osumilite are discussed and re-assigned. The spectra are re-interpreted on the basis of the distribution of Fe2+ in these minerals over structural octahedral and tetrahedral positions.
Keywords: tuhualite; beryl; cordierite; osumilite; optical spectra; iron ions; electronic dd transitions; intervalence charge-transfer transitions